The Satisfaction Analysis of Local Public Transportation (Carry) Services at Batam, Indonesia - Jeffrey Victory; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Carry is one of the public transportation found in Batam, Indonesia. However, there is a need for innovation so that this public transportation can compete with other public transportation and private vehicles. Therefore, this study was carried out to determine what variables must be considered when determining the level of public satisfaction with "Carry." First, the data collection method is to distribute questionnaires to 131 respondents through google forms. Then the analysis method uses IPA (Importance Performance Analysis), which is presented as a diagram with four quadrants. The results show that the user satisfaction level is 2.85 to 3.45. In contrast, the user importance level is in the range of 4.29 to 4.68, with a gap between -0.94 to -1.68. Finally, based on the study's findings, it can be determined that the variables cleanliness of public transportation facilities, the safety of service users, comfort of service users, and availability of facilities/interiors are placed in quadrant A, requiring special attention.